Preparation of highly active phosphated TiO2 catalysts via continuous sol–gel synthesis in a microreactor. Issue 17 (13th August 2019) - Martin, O.; Bolzli, N.; Puértolas, B.; Pérez-Ramírez, J.; Riedlberger, P.
Abstract : Highly efficient TiO2 based catalysts for biomass conversion were obtained through optimised and well-controlled sol–gel synthesis in a multi-mixer microreactor. Abstract : Microreactors, featuring μm-sized tubes, offer greater flexibility and precise control of chemical processes compared to conventional large-scale reactors, due to their elevated surface-to-volume ratio and modular construction. However, their application in catalyst production has been largely neglected. Herein, we present the development of a microreactor process for the one-step sol–gel preparation of phosphated TiO2 – a catalyst which has been recently demonstrated to be an eco-friendly material for the selective synthesis of the platform chemical 5-hydroxymethylfurfural (5-HMF) from bio-derived glucose. In order to establish catalyst preparation–property–performance relationships, 18 samples were prepared according to a D-optimal experimental plan with a central point. The key properties of these samples (porosity, crystallite size, mole bulk fraction of P) were correlated, using quadratic and interaction models, with the catalytic performance (conversion, selectivity, reaction rate) of 5-HMF synthesis as a test reaction. The optimal calculated catalyst features were set as target parameters to optimise catalyst synthesis applying quadratic correlation functions. An optimal catalyst was obtained, validating the models employed, with a yield of almost 100% and a space–time yield of ca. 3 orders of magnitude higher than that of a conventional batch process (26.8 vs. 0.07 gcat h −1 cmreactor −3 ). The high yield could be mainly attributed to the optimal hydrolysis ratio and temperature. Controlling the TiO2 crystallite size and surface acidity in conjunction with fine-tuning of the porous properties in the microreactor led to increased glucose conversion (95.6 vs. 78.7%), surface based formation rates of 5-HMF (0.047 vs. 0.008 g5-HMF h −1 mcat −2 ), and selectivity towards 5-HMF (55.5 vs. 50.0%) of the optimal catalyst in relation to the batch-prepared material.